Poverty and Inequality Maps for Rural Vietnam : An Application of Small Area Estimation - Cuong, Nguyen Viet; Truong, Tran Ngoc; van der Weide, Roy (2012)
The objective of the paper is to update the small area estimates of poverty and inequality for rural Vietnam. The new estimates of province and district level poverty for the year 2006, when combined with estimates available for 1999, allow for examination of how poverty has changed in rural Vietnam over the past seven years. The analysis finds that all provinces across the country experienced a noticeable reduction in rural poverty during the period 1999-2006. Some of the largest reductions in poverty are observed for provinces with poverty rates close to the national average. The poorest provinces have also experienced reductions in poverty, albeit at a more modest pace. Provinces and districts with lower levels of inequality in 2006 have seen above average poverty reductions. The authors consider both expenditure and income based measures of poverty and inequality, and find the results to be very similar.